Persentase Bobot Karkas dan Potongan Komersial Ayam Sentul-G3 yang Diberi Ransum Mengandung Dedak Tinggi dengan Suplementasi Fitase dan ZnO - Cecep Hidayat; . Sumiati; Sofjan Iskandar (Institut Pertanian Bogor, 2015)
This experiment aimed to determine the effect of phytase enzyme and ZnO supplementation on the percentage of weight of carcass, commercial cuts, abdominal fat of males, and females of Sentul-G3 chicken fed high rice bran diet. There are nine treatments, R1 = 50% commercial diet: 50% rice bran; R2 = R1 + 1.5 g ZnO/kg; R3 = R1 + 3.2 g ZnO/kg; R4 = R1 + phytase 1.000 U/kg; R5 = R1 + (phytase 1.000 U/kg + 1.5 g ZnO/kg); R6 = R1 + (phytase 1.000 U/kg + 3.2 g ZnO / kg); R7 = R1 + phytase 2.000 U/kg; R8 = R1 + (phytase 2.000 U/kg + 1.5 g ZnO/kg); dan R9 = R1 + (phytase 2.000 U/kg + 3.2 g ZnO/kg). Each experimental unit consisted of 6 animals unsexed local chicken Sentul-G3. Beside that, used commercial diet treatment. Parameters observed were percentage of weight of carcass, commercial cuts, abdominal fat of males, and females of Sentul-G3 chicken. The experimental results showed that the diet treatment did not gave effect to percentage of weight of male and female carcass, male and female backs, the female wings, upper thights and abdominal fat of male and female chickens Sentul-G3. Diet treatments gave varies effect to weight percentage of male and female breast, upper thighs female, male and female lower thighs chicken Sentul-G3. The combination of 2.000 U phytase and 3.2 g of ZnO/kg diet lowers weight percentage of male wings. Supplementation of 1.5 g ZnO/kg diet increases abdominal fat deposition.